Force, acceleration and velocity during trampoline jumps - a challenging assignment - Pendrill, A.-M.; Ouattara, L. (Physics Education, 2017)
Bouncing on a trampoline lets the jumper experience the interplay between weightlessness and large forces on the body, as the motion changes between free fall and large acceleration in contact with the trampoline bed. In this work, several groups of students were asked to draw graphs of elevation, velocity and acceleration as a function of time, for two full jumps of the 2012 Olympic gold medal trampoline routine by Rosannagh MacLennan. We hoped that earlier kinaesthetic experiences of trampoline bouncing would help students make connections between the mathematical descriptions of elevation, velocity and acceleration, which is known to be challenging. However, very few of the student responses made reference to personal experiences of forces during bouncing. Most of the responses could be grouped into a few categories, which are presented and discussed in the paper. Although the time dependence of elevation was drawn relatively correctly in most cases, many of the graphs of velocity and acceleration display a lack of understanding of the relation between these different aspects of motion.